Projekts: Uzņēmuma "Jumis Finances" dibināšana - Tkačenko, Andrejs (Latvijas Universitāte, 2017)
Maģistra darba mērķis ir izstrādāt jauna uzņēmuma dibināšanas plānu un biznesa plānu trim darbības gadiem. Maģistra darba gaitā darba autors izstrādāja un novērtēja izveidojamā uzņēmuma „Jumis Finances” dibināšanas plānu un biznesa plānu trim pirmajiem darbības gadiem. Projekta mērķis – dibināt neatkarīgu uzņēmumu, kas nodarbosies ar vērtspapīru individuālu portfeļu izstrādi un konsultāciju sniegšanu. Darbs izklāstīts uz 101 lapām un iekļauj izmantotās literatūras un citu informācijas avotu 46 nosaukumus, 26 tabulas, un17 attēlus. Darba pētīšanas metodes: statistiskā analīze, grafiskā analīze, vertikāla analīze, SVID analīze, riska matrica.

The aim of master work is to develop plan for the formation of a new company and business plan for three years. The author's work was opening and establishing the company„Jumis Finances”finance plan and the business plan for the first three years of operation. The aim of the project – to create an independent company dedicated to the development of individual securities portfolios and the provision of advice for consumers. It is necessary to encourage investors to invest its free funds by financial bonds, which not only will help investors to increase their investment, but will also contribute to the economy with new money inflows. Work out to 101 pages and included the names and other information sources, 92, 46 tables, and 29 images. Working methods: statistical analysis, graphical analysis, vertical analysis, the SWOT analysis, the risk matrix.
Project: Establishment of "Jumis Finances"
Keywords: Finanses un kredīts; ieguldījumu pārvaldes sabiedrības/ investment management firms; investīcijas/ investment; ieguldījumu fondi/ investment funds; akcijas/ shares; obligācijas/ bonds